Implementation Analysis of Employee Job Descriptions as Supporting the Development of Pisang Umkm Segading Ponorogo - Agustin Rani Nurfadila; Palmadi Putri Surya Negara; Ilham Prasetyo Utomo (Agroindustrial Technology Journal, 2023)
A job description is a division of work tasks for employees that aims to ensure that employees have responsibility for their respective jobs, which have been divided by their superiors. This research aims to encourage companies to consider the placement of human resources in their respective jobs. The method used is a survey and direct interviews with business owners using an open questionnaire to obtain data on the business. The data sources used are business owners, places or events, and employees at the Pisang Segading Ponorogo MSME business. Based on the research results, it can be concluded that the UMKM Pisang Segading Ponorogo has not implemented job descriptions properly for three employees, so employees still often work concurrently with eight working hours so that the impact of the product produced does not meet the production target of 25 kg, apart from that in the UMKM Pisang Segading Ponorogo also does not yet have an organizational structure so that employee placements are still not well structured. Efforts made to address these obstacles are by adding employees by threatening employees and employees at the Pisang Segading Ponorogo UMKM by providing job descriptions so that they will be more focused and productive in their respective jobs. So, the solution above can support the progress and curiosity of UMKM Pisang Segading Ponorogo.